2006
DOI: 10.1097/01.wnr.0000223392.82198.6d
|View full text |Cite
|
Sign up to set email alerts
|

Are you ready? I can tell by looking at your microsaccades

Abstract: The direction of microsaccades has been shown to be biased by the allocation of spatial attention. Here, we investigated whether the cognitive processes involved in preparing to respond to an upcoming target can modulate the microsaccadic response. Specifically, we found that optimal manual response preparation, reflected by faster response times, was associated with a reduction in the absolute frequency of microsaccades. The present results are consistent with previous studies suggesting a relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 14 publications
8
86
0
Order By: Relevance
“…There is accumulating evidence that the analysis of the timing, rate, and direction of microsaccades provide information about the neural mechanisms underlying vision and certain higher-order cognitive behaviors. For example, microsaccades, which modulate neural activity in visual areas (Martinez-Conde et al, 2000Snodderly et al, 2001;Herrington et al, 2009;Hafed and Krauzlis, 2010;Hass and Horwitz, 2011), have also been shown to be correlated with visual awareness and visuospatial attention (Hafed and Clark, 2002;Engbert and Kliegl, 2003;Laubrock et al, 2005;Betta and Turatto, 2006;Engbert, 2006;Otero-Millan et al, 2008;Cui et al, 2009;Herrington et al, 2009;Kliegl et al, 2009;Pastukhov and Braun, 2010). Given that the temporal dynamics of each eye can differ throughout a given microsaccade, our results suggest that the knowledge of the motion of both eyes could improve the correlation observed between microsaccades and neural activity (or behavior).…”
Section: Binocular Microsaccades and The Implication For Studies Of Vmentioning
confidence: 68%
See 1 more Smart Citation
“…There is accumulating evidence that the analysis of the timing, rate, and direction of microsaccades provide information about the neural mechanisms underlying vision and certain higher-order cognitive behaviors. For example, microsaccades, which modulate neural activity in visual areas (Martinez-Conde et al, 2000Snodderly et al, 2001;Herrington et al, 2009;Hafed and Krauzlis, 2010;Hass and Horwitz, 2011), have also been shown to be correlated with visual awareness and visuospatial attention (Hafed and Clark, 2002;Engbert and Kliegl, 2003;Laubrock et al, 2005;Betta and Turatto, 2006;Engbert, 2006;Otero-Millan et al, 2008;Cui et al, 2009;Herrington et al, 2009;Kliegl et al, 2009;Pastukhov and Braun, 2010). Given that the temporal dynamics of each eye can differ throughout a given microsaccade, our results suggest that the knowledge of the motion of both eyes could improve the correlation observed between microsaccades and neural activity (or behavior).…”
Section: Binocular Microsaccades and The Implication For Studies Of Vmentioning
confidence: 68%
“…Although they were once thought to play no role in visual perception (Kowler and Steinman, 1979), recent work suggests that these small fixational eye movements serve many important functional roles. For example, microsaccade propensity and direction have been shown to be highly informative about the allocation of attention (Hafed and Clark, 2002;Engbert and Kliegl, 2003;Betta and Turatto, 2006;Pastukhov and Braun, 2010). Accordingly, correlations between microsaccade generation and neural activity are currently used to investigate higher cognitive behaviors as well as the basis of certain neurological disorders (Engbert, 2006;Martinez-Conde, 2006;Martinez-Conde et al, 2009;OteroMillan et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a dependence of slowing on microsaccade direction remains possible due to global interactions that spatially bias the competing processes (Rolfs, Kliegl, & Engbert, 2008;Rolfs, Laubrock, & Kliegl, 2008). However, slower RTs have also been associated with higher microsaccade rates in a task requiring manual responses to visual targets presented in the fovea (Betta & Turatto, 2006). These authors oVered several explanations for their results.…”
Section: Rt Costs Of Target-congruent Microsaccadesmentioning
confidence: 87%
“…Betta and Turatto (2006) also reported that faster responses are associated with a reduction in microsaccade rate. In the present data, this microsaccade-related slowing is only observed when one of the task elements-cue or target-is visual.…”
Section: Microsaccade-related Slowingmentioning
confidence: 93%
“…We also imposed a minimum intersaccadic interval of 20 ms so that overshoot corrections were not categorized as microsaccades (Møller et al, 2002;OteroMillan et al, 2008;Troncoso et al, 2008a). One subject produced microsaccades that were often larger than 1°; thus, we chose a maximum microsaccade magnitude threshold of 2° (Betta and Turatto, 2006;Martinez-Conde et al, 2006;Troncoso et al, 2008a). Across subjects, Ͼ85% of all microsaccades were smaller than 1°.…”
Section: Eye Movements Recordings and Analysesmentioning
confidence: 99%